COMPARISON OF BANK PERFORMANCE ON THE BANK OWNERSHIP OF KOREAN BANK - Milach, Azki Zainal; Pracoyo, Antyo; Simatupang, Batara Maju; Putri, Vidiyanna Rizal (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research aims to analyze the financial performance of banks based on Korean bank ownership from the second quarter of 2019 to the third quarter of 2023. This study employs a descriptive research type with a quantitative approach. Findings on the liquidity ratio show that the average Loan to Deposit Ratio (LDR) exceeds 92%, which is above the standard set by Bank Indonesia. For the profitability ratio, the average Return on Assets (ROA) ratio of most banks falls below 1.5%, below the benchmark established by Bank Indonesia. In the Capital Adequacy Ratio (CAR) analysis, the CAR exceeds 10%, which is above the standard set by the Financial Services Authority (OJK). In the solvency ratio analysis, the average Debt to Equity Ratio (DER) of most banks is below 4.22 times, which is under the benchmark published by the Indonesia Stock Exchange (IDX) as of June 2024.